FORMATION OF SOCIAL RESPONSIBILITY OF YOUNG PEOPLE IN THE PROCESS OF OBTAINING HIGHER EDUCATION - Kolomiiets, Lesia; Shulga, Galyna; Lebed, Iuliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In the article the problem of the formation of social responsibility of young people in the process of obtaining higher education is actualized at the theoretical, normative-legal and empirical level. On the basis of diagnostics and a focus group survey, the importance and lack of implementation of the problem of the formation youth social responsibility in the modern realities of the activities of higher educational institutions was proved. It was found that the work of higher educational institutions on the formation of social responsibility is considered by applicants for higher education not to be systemic, oversaturated with education. It was stated that, in the opinion of applicants for higher education, the process of forming social responsibility will be more effective if they are included in socially responsible activities, familiarize themselves with the opportunity to work alongside socially active citizens, get involved in various projects, gain experience in socially responsible behaviour, and spend meaningful leisure. The foreign and domestic experience of the formation of the social responsibility of youth is analyzed. A description of the author's program of the formation of social responsibility of young people in the process of obtaining higher education is proposed, the testing of which has led to positive dynamics in the state of social responsibility of young people.